Progressive Muscle Relaxation And Stretching Interventions On Reducing Physical Fatigue And Injury Risk In Perioperative Nurses - Nadhifah Eka Cahyani; Tri Johan Agus Yuswanto (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Background: Physical fatigue is a major challenge frequently encountered by perioperative nurses due to high workload, long working hours, emotional pressure, and a demanding environment requiring continuous concentration and physical endurance. The purpose of this study was to analyze the effectiveness of progressive muscle relaxation and stretching methods used by perioperative nurses on fatigue levels and injury risk. Methods: This quasi-experimental study involved 120 perioperative nurses recruited by purposive sampling and assigned to two groups: an experimental group receiving progressive muscle relaxation (PMR) and a comparison group performing stretching exercises. Physical fatigue and injury risk were measured using the IFRC questionnaire and a researcher-developed injury risk questionnaire before and after intervention. Data were analyzed using the Mann-Whitney test with a significance level of α = 0.05. Results: The primary outcomes showed a significant reduction in physical fatigue and injury risk in both groups after intervention (p < 0.05). The PMR group demonstrated a greater decrease in fatigue levels compared to the stretching group (effect size = [insert effect size]). Additionally, the risk of injury was significantly lower post-intervention in the PMR group. No significant changes were observed in the control or baseline measures. These findings indicate that both PMR and stretching are effective in reducing fatigue and injury risk, with PMR showing superior effectiveness. Conclusion: The study supports the implementation of progressive muscle relaxation and stretching exercises as practical, low-cost strategies to reduce physical fatigue and injury risk among perioperative nurses, contributing to improved occupational health and safety in hospital settings.